Architectural Synthesis of Fixed-Point DSP Datapaths Using FPGAs - Gabriel Caffarena; Juan A. López; Gerardo Leyva; Carlos Carreras; Octavio Nieto-Taladriz (International Journal of Reconfigurable Computing)
We address the automatic synthesis of DSP algorithms using FPGAs. Optimized fixed-point implementations are obtained by means of considering (i) a multiple wordlength approach; (ii) a complete datapath formed of wordlength-wise resources (i.e., functional units, multiplexers, and registers); (iii) an FPGA-wise resource usage metric that enables an efficient distribution of logic fabric and embedded DSP resources. The paper shows (i) the benefits of applying a multiple wordlength approach to the implementation of fixed-point datapaths and (ii) the benefits of a wise use of embedded FPGA resources. The use of a complete fixed-point datapath leads to improvements up to 35%. And, the wise mapping of operations to FPGA resources (logic fabric and embedded blocks), thanks to the proposed resource usage metric, leads to improvements up to 54%.